2013
DOI: 10.1212/wnl.0b013e31828c2e9e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pathologic insights from latent HIV-1 infection in the human brain

Abstract: Objective: We aimed to investigate whether HIV latency in the CNS might have adverse molecular, pathologic, and clinical consequences.Methods: This was a case-control comparison of HIV-1 seropositive (HIV1) patients with clinical and neuropathologic examination. Based on the levels of HIV-1 DNA, RNA, and p24 in the brain, cases were classified as controls, latent HIV CNS infection, and HIV encephalitis (HIVE). Analysis of epigenetic markers including BCL11B, neurodegeneration, and neuroinflammation was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 34 publications
(37 reference statements)
3
159
0
2
Order By: Relevance
“…A huge amount of HIV-1 DNA in the peripheral blood has been associated with severe neurocognitive impairment, independently of HIV-1 RNA plasma load [21]. In the setting of virologic suppression following ART, greater HIV-1 DNA levels contribute to persistent immune activation in tissues, including the brain [22], which in turn contributes to neurodegeneration and cognitive impairment [23]. Finally, there is evidence that the cerebrospinal pool of HIV-1 is one of the major obstacles to eradication [24] and therefore strategies to make ARVs overcome the BBB are urgently needed.…”
Section: Anatomical Sites: Central Nervous System Male Genital Tractmentioning
confidence: 99%
“…A huge amount of HIV-1 DNA in the peripheral blood has been associated with severe neurocognitive impairment, independently of HIV-1 RNA plasma load [21]. In the setting of virologic suppression following ART, greater HIV-1 DNA levels contribute to persistent immune activation in tissues, including the brain [22], which in turn contributes to neurodegeneration and cognitive impairment [23]. Finally, there is evidence that the cerebrospinal pool of HIV-1 is one of the major obstacles to eradication [24] and therefore strategies to make ARVs overcome the BBB are urgently needed.…”
Section: Anatomical Sites: Central Nervous System Male Genital Tractmentioning
confidence: 99%
“…It interacts with bromodomains, exhibiting the highest specificity in Brd4. Recently, several lines of evidence indicated that JQ1 reactivates latent HIV in both the clonal and primary cell model of HIV latency, providing evidence for its multifunctional utility [22,36] . Specifically, it inhibits recognition of acetylated lysines relevant to actively transcribed chromatin by binding to the bromodomain-binding pocket.…”
Section: Therapeutics Used In Reactivating Latent Virusmentioning
confidence: 99%
“…An abundance of Sp3 relative to Sp1 in astrocytes can, in some part, explain the restriction of HIV-1 transcription within these cells [35] . In addition, Desplats and his colleagues reported that levels of BCL11B, heterochromatin protein 1 (HP1)α, methyl CpG binding protein 2 (MeCP2), and histone deacetylase 1 (HDAC1) were significantly increased in CNS cells latently infected with HIV-1, favoring the idea that epigenetic factors are involved in silencing mechanisms [36] .…”
Section: Introductionmentioning
confidence: 99%
“…The neurodegenerative disease (neuroAIDS) progresses during chronic infection, with neurocognitive, behavioral, and motor impairments that can lead to full-blown HIV-associated dementia [58]. The mechanisms by which HIV causes neurodegeneration are not fully elucidated, and include both host and viral mechanisms [28,63]. Additional relevant contributions to neuroAIDS are caused by reactivation of bystander latent/persistent viruses with neurotropic potential such as EBV, cytomegalovirus, and JC polyomavirus, which can result in life-threatening CNS infections in immunocompromised hosts [28].…”
Section: Msrv/herv-w/syncytin-1 Endogenous Retroviruses and Hiv-relatmentioning
confidence: 99%